PENGARUH SOSIALISASI ANTISIPATIF, PENGHARGAAN DAN INTENSITAS MORAL TERHADAP INTENSI WHISTLEBLOWING - Prayoga, Ichwan Gusti; Purwati, Atiek Sri; Wuladari MA, Ratu Ayu Sri (Soedirman Accounting, Auditing and Public Sector Journal, 2023)
This study aims to investigate the effect of anticipatory socialization, reward, and moral intensity on on whistleblowing intentions. This study is a quantitative research with a survey method using questionnaire to collect the data. The population in this study were employees of the Regional Inspectorate of Banyumas, Purbalingga, Banjarnegara, Cilacap, and Kebumen Regency. The sampling technique used is purposive sampling. A total of 145 employees of the inspectorate became respondents in this study. Based on the result of multiple regression analysis test, it indicates that anticipatory socialization, reward, and moral intensity have positif effect on whistleblowing intentions.